Obsessive–compulsive disorder patients have a reduced sense of control on the illusion of control task - Gillan, Claire M.; Morein-Zamir, Sharon; Durieux, Alice; Fineberg, Naomi A.; Sahakian, Barbara J.; Robbins, Trevor W. (Frontiers in Psychology, 2014)
There is disagreement regarding then role of perceived control in obsessive-compulsive disorder (OCD). The present study used a traditional illusion of control paradigm (Alloy & Abramson, 1979) to empirically test control estimation in OCD. Twenty-six OCD patients and 26 matched comparison subjects completed an illusion of control task wherein their goal was to attempt to exert control over a light bulb. The density of reinforcement (high, low) and the valence of trials (gain, loss) were experimentally manipulated within subjects. Unbeknownst to participants, the illumination of the light bulb was predetermined and irrespective of their behavior. OCD patients exhibited lower estimates of control compared with healthy comparison subjects. There were no interactions between group and outcome density or group and valence. We found that OCD patients endorse lower estimates of control than comparison subjects. This finding highlights a potential role for contingency learning in the disorder.